Validity and Reliability of the Persian Version of Brace Questionnaire for Assessing the Quality of Life Life in Subjects With Scoliosis - Fahimeh Sadat Jafarian; Ebrahim Sadeghi Demneh (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: Spinal deformity can affect the Quality Of Life (QOL) of all people, especially young adults. Scoliosis is one of the most common types of this disorder with unknown etiology. World health organization defines QOL as the individuals' perception of their position in life, based on individual and cultural characteristics in which they live. The right tools to assess QOL can provide valuable clinical and research results. Questionnaires are considered to be the most available and cheapest possible tool for measuring this variable. Brace Questionnaire (BrQ) is one of these tools designed for this purpose. To our knowledge, only the Italian, English, and Polish versions of this questionnaire are available. Thus, this study aimed to translate and determine the validity and reliability of the Persian version of BrQ. Materials & Methods: Fifty subjects (Mean±SD age: 15.41±1.77 years) with scoliosis participated in this study. All of them had a history of wearing spinal braces for at least four months. They entered into the study based on the inclusion criteria and signed a written consent form. The BrQ has 34 self-reported items and eight domains of general health perception, physical functioning, emotional functioning, self-esteem and aesthetics, vitality, school activity, bodily pain, and social functioning. Participants by completing this tool express their feelings during the past one and three months. First, a confirmation email was received from the developer of the questionnaire to perform the translation and psychometric evaluation. It was translated through six stages based on Beaton's guidelines. First, three bilingual speakers (native in English and Persian) forward translated the original version. Next, specialists and interpreters compared two translated drafts. The next steps included a backward translation of the initial translated version, sending the English version to the developer for appraisal, and receiving confirmation that it is identical to the original version. Finally, the initial Persian version was sent to 10 orthotics and prosthetists and ten patients with scoliosis (pilot study) to examine its face validity. The approved pre-version was considered as the final Persian version of BrQ (BrQ-P). Subsequently, The BrQ-P and Scoliosis Research Society (SRS-22r) questionnaire were completed by 50 participants to assess BrQ-P validity. To determine test-retest reliability, the questionnaires were completed by the same participants after seven days. The obtained data were analyzed in SPSS V. 17. The statistical significance level was set at P<0.05. Results: All participants in the pilot study confirmed that all items were easy to understand. The internal consistency of BrQ-P using the Cronbach α was at an acceptable level (0.935). The intraclass correlation coefficient was obtained 0.93 at a 95% confidence interval (0.90-0.95), indicating its good test-retest reliability. Moreover, the relationship between BrQ-P and SRS-22r using the Pearson correlation coefficient was obtained 0.90, indicating a significant relationship between these two questionnaires (P<0.001). Conclusion: The BrQ-P is a valid and reliable tool to assess the QOL of people with scoliosis.